2021
DOI: 10.3390/app11125464
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Patient-to-Image Surface Registration Technique for ENT- and Neuro-Navigation Systems: Proper Point Set in Patient Space

Abstract: Patient-to-medical image registration is a crucial factor that affects the accuracy of image-guided ENT- and neurosurgery systems. In this study, a novel registration protocol that extracts the point cloud in the patient space using the contact approach was proposed. To extract the optimal point cloud in patient space, we propose a multi-step registration protocol consisting of augmentation of the point cloud and creation of an optimal point cloud in patient space that satisfies the minimum distance from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…This result showed that it was slightly better compared to the previous results that tried to reduce the SRE by extracting a new point-cloud. Yoo et al 7 and Choi et al 15 achieved 1.53-2.23 and 1.79-3.32 mm, respectively, using their novel surface registration methodologies. Additionally, the results proposed in this study are quite close to the point-registration standard of 1.0 mm or less, 46,47 which requires relatively high registration accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result showed that it was slightly better compared to the previous results that tried to reduce the SRE by extracting a new point-cloud. Yoo et al 7 and Choi et al 15 achieved 1.53-2.23 and 1.79-3.32 mm, respectively, using their novel surface registration methodologies. Additionally, the results proposed in this study are quite close to the point-registration standard of 1.0 mm or less, 46,47 which requires relatively high registration accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Yoo et al 7 . and Choi et al 15 . achieved 1.53–2.23 and 1.79–3.32 mm, respectively, using their novel surface registration methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method showed an obvious speed advantage (17.4s and 21.4s for the elastic phantom and five patients, respectively) as well as an improvement in registration accuracy (1.17 ± 0.04 mm and range 1.64 mm to 1.83 mm for the elastic phantom and five patients, respectively). Choi et al [20] extracted the optimal pointcloud that has the minimum distance from the point-cloud in image space. The optimal point-cloud was used to improve surface registration accuracy, and it was validated using a hemisphere mathematical model and a plastic facial phantom.…”
Section: Related Workmentioning
confidence: 99%
“…Accordingly, a surface registration method has been proposed [1,10]. Related studies have been conducted to improve registration accuracy that is relatively low compared to point registration [1,2,9,10,12,17,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%